TI_GERICHTE 12.2018.78 vom 3. September 2018 , Società a garanzia limitata - diritto a ragguagli e a consultare documenti - TI Tribunale d'appello (2018)
Società a garanzia limitata - diritto a ragguagli e a consultare documenti